2012
DOI: 10.1016/j.mehy.2012.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Could cadmium be responsible for some of the neurological signs and symptoms of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome

Abstract: a b s t r a c tAccording to the World Health Organization, Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/ CFS) is a neurological disease characterized by widespread inflammation and multi-systemic neuropathology. Aetiology and pathogenesis are unknown, and several agents have been proposed as causative agents or as factors perpetuating the syndrome. Exposure to heavy metals, with particular reference to mercury and gold in dental amalgams, has been considered among the triggers of ME/CFS. Here we hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Our transcranial technique for viewing meningeal and cortical structures ultrasonographically has been previously published as part of a study of patients with myalgic encephalomyelitis and chronic fatigue syndrome (ME/CFS) (Pacini et al, 2012). The TUS normal anatomical observations were recently published by the Italian Journal of Anatomy and Embryology [volume 188(3) 2013, Figure 2].…”
Section: Methodsmentioning
confidence: 99%
“…Our transcranial technique for viewing meningeal and cortical structures ultrasonographically has been previously published as part of a study of patients with myalgic encephalomyelitis and chronic fatigue syndrome (ME/CFS) (Pacini et al, 2012). The TUS normal anatomical observations were recently published by the Italian Journal of Anatomy and Embryology [volume 188(3) 2013, Figure 2].…”
Section: Methodsmentioning
confidence: 99%
“…Clinically, humans with elevated blood or urine Cd demonstrate decreased attention level and memory [81]. Additionally, humans with high urinary Cd levels had significantly decreased low-frequency hearing [82].…”
Section: Clinical Toxicitymentioning
confidence: 99%
“…We previously demonstrated that cadmium may be responsible for the neurological signs and symptoms of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome and for abnormalities of breast cancer cell-induced angiogenesis (14,15). In the subject, cadmium in the urine exceeded twice the maximum expected value at baseline in August.…”
Section: Cadmiummentioning
confidence: 92%